2022
DOI: 10.3390/agronomy12030592
|View full text |Cite
|
Sign up to set email alerts
|

Effective Biocontrol of Rice Blast through Dipping Transplants and Foliar Applications

Abstract: Rice (Oryza sativa) is an increasingly popular food in Africa. As much as 30% of yields are lost due to blast disease caused by Magnaporthe oryzae. Several commercial biopesticides of Bacillus subtilis, Trichoderma asperellum, and Serratia sp. strains were evaluated under field conditions for their effects against rice blast and yield at one site in Kenya and three sites in Tanzania in 2020 and 2021. Each biopesticide was applied as a dipping treatment at transplanting, post-transplanting foliar spraying, or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Among bacterial endophytes, the highest inhibition was found by B. licheniformis, followed by Stenotrophomonas rhizophila. Some of the known biocontrol agents namely Trichoderma species, Bacillus subtilis and Pseudomonas fluorescens have shown good results in managing rice blast [9][10][11]. The identified endophytes used in the study were found as good as other reported biocontrol agents for managing rice blasts.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Among bacterial endophytes, the highest inhibition was found by B. licheniformis, followed by Stenotrophomonas rhizophila. Some of the known biocontrol agents namely Trichoderma species, Bacillus subtilis and Pseudomonas fluorescens have shown good results in managing rice blast [9][10][11]. The identified endophytes used in the study were found as good as other reported biocontrol agents for managing rice blasts.…”
Section: Discussionmentioning
confidence: 64%
“…Chemical fungicides are often used, resulting in the development of resistance to pathogens, environmental contamination, and effects on non-target microorganisms [8]. Biocontrol using endophytic microorganisms is an alternative management strategy and is being used throughout the world for the management of rice blast [9][10][11]. An endophyte is a fungal or bacterial microbe that spends all or part of its life cycle inhabiting the host plant's healthy tissues, usually without persuading disease symptoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cultural, chemical, and biological strategies have been developed and deployed to control this disease. Biological control, such as the use of biocontrol agents 5 , 6 and deployment of resistant cultivars, is an eco-friendly approach. However, wide application, effectiveness, and durability can be achieved only through the identification of stable resistant sources and their utilization in crop breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Matrine, a tetracyclo-quinolizidine compound, exists in various leguminous plants such as Sophora flavescens Ait., S. alopecuroides L., and S. tonkinensis Gapnep. Matrine is widely used in medicine to treat various diseases and can be used to control pests and diseases in agriculture because it has a wide spectrum of activities, including insecticidal, antibacterial, antifungal, and antiviral activities [9][10][11][12][13]. More significantly, matrine degrades easily in soil and water [14,15] and is nontoxic to nontarget organisms [16].…”
Section: Introductionmentioning
confidence: 99%